A novel model for malware propagation on wireless sensor networks - Angel Martin-del Rey (Mathematical Biosciences and Engineering, 2024)
The main goal of this work was to propose a novel mathematical model for malware propagation on wireless sensor networks (WSN). Specifically, the proposed model was a compartmental and global one whose temporal dynamics were described by means of a system of ordinary differential equations. This proposal was more realistic than others that have appeared in the scientific literature since. On the one hand, considering the specifications of malicious code propagation, several types of nodes were considered (susceptible, patched susceptible, latent non-infectious, latent infectious, compromised non-infectious, compromised infectious, damaged, ad deactivated), and on the other hand, a new and more realistic term of the incidence was defined and used based on some particular characteristics of transmission protocol on wireless sensor networks.